Training To Be A Community Psychologist In The Age Of A Digital Revolution - Bell, Sherry; van den Berg, Martin; Liboro, Renato M. (Engaged Scholar Journal, 2023)
Reflecting on pedagogy and curricula that have shaped the field of community psychology, we review the history of training community psychologists since the field’s inception in the United States. We then examine relevant academic literature documenting how digital technologies in the 21st century have been successfully used in community-based participatory research (CBPR) studies conducted by community psychologists to promote engaged scholarship, the field’s core values (e.g. sense of community, social justice, collaboration), and its commitment to social change. While early ideas for improving scholars’ training emphasized adopting practices to meet changing community needs, our review of literature on CBPR and other community-engaged scholarly work by community psychologists in the last two decades has revealed that digital technologies’ ability to promote the field’s values and goals still needs to be fully harnessed. Lastly, we offer practical recommendations for community psychology undergraduate and graduate training programs to consider and implement so they can incorporate digital technologies into their programs and harness their potential to promote engaged scholarship, the field’s core values, and its commitment to social change.